Development of An Artificial Intelligence-Based Islamic Religious Education Curriculum to Improve Learning Quality - Ali, Ridwan; Jamin, Hanifuddin; Iqbal, Muhammad (Teunuleh Publisher, 2025)
The development of an Artificial Intelligence (AI)-based Islamic Religious Education (PAI) curriculum has become an urgent necessity in today’s digital era. An AI-based curriculum offers a more personalized, adaptive, and interactive learning approach, thereby enhancing the effectiveness and relevance of religious education in addressing the challenges of the 21st century. Using a qualitative approach with a library research method, this study examines how AI can be integrated into the objectives, content, methods, and assessment of PAI learning. In addition, it explains the benefits and implications for teachers, students, and educational institutions. The findings of this study indicate that: 1. The development of an AI-based Islamic Religious Education (PAI) curriculum has proven to be a strategic approach to improving the quality of learning in the digital era, 2.The implementation of AI in PAI learning has a positive impact on teachers and students. For teachers, AI enhances instructional efficiency and assists in analyzing and detecting students’ learning difficulties more accurately, 3. The successful implementation of an AI-based PAI curriculum is highly dependent on systemic and collaborative support. Synergy among policymakers, educators, and technology developers is required to ensure that the developed curriculum remains humanistic, value-oriented, and sustainable.